The "Private School Advantage" in Argentina - Fischman, Gustavo E. (Education Policy Analysis Archives, 2001)
Local actors' perceptions of curricular and management changes in two private schools and one neighboring public secondary school in the city of Buenos Aires, Argentina, are analyzed. An exploration was conducted of how, within an ideologically and politically pro-reform context and a widespread acceptance of the "private school advantage," principals, teachers, and students in these schools evaluated the changes (or lack of them) in management, teaching, and curriculum orientations of the secondary education sector.